2018
DOI: 10.1007/s00405-018-5128-8
|View full text |Cite
|
Sign up to set email alerts
|

Cartilaginous Eustachian tube length and carotid canal dehiscence in children: a radiological study

Abstract: Carotid canal dehiscence in children has a low prevalence. Variation in the length of the cartilaginous Eustachian tube is low but is correlated with age. More research is required to define the indications, safety, efficacy and technical aspects of BET in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These studies reported a mean cartilaginous ET length of 24.5 mm in children 18 and 26.7 mm in adults 11 . Unlike the current study, these studies measured the cartilaginous ET on CT to the nearest 0.1 mm by using scans with a slice thickness of 0.63 mm 18 or 0.67 mm 11 . However, these studies compared the ET in a pediatric‐versus‐adult cohort.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These studies reported a mean cartilaginous ET length of 24.5 mm in children 18 and 26.7 mm in adults 11 . Unlike the current study, these studies measured the cartilaginous ET on CT to the nearest 0.1 mm by using scans with a slice thickness of 0.63 mm 18 or 0.67 mm 11 . However, these studies compared the ET in a pediatric‐versus‐adult cohort.…”
Section: Discussionmentioning
confidence: 81%
“…These findings are consistent with previous studies that measured the cartilaginous ET on CT imaging. These studies reported a mean cartilaginous ET length of 24.5 mm in children 18 and 26.7 mm in adults. 11 Unlike the current study, these studies measured the cartilaginous ET on CT to the nearest 0.1 mm by using scans with a slice thickness of 0.63 mm 18 or 0.67 mm.…”
Section: Discussionmentioning
confidence: 97%
“…Also, passive smoke exposure was reported to increase the risk of otitis media in children, but this has not been reported in adults [33]. The eustachian tube is short in children, but in adults it is long and normally closed [34, 35]. That suggests that tobacco smoke does not readily enter the middle ear of adults, resulting in less or no risk of otitis media.…”
Section: Discussionmentioning
confidence: 99%